Theory of Planned Behavior to Analyze the Intention to Use the Electronic Money - Prayidyaningrum, Shabrina; Djamaludin, Moh Djemdjem (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This study aimed to analyze the knowledge, attitude, and purchase intention on electronic money among undergraduate students approached by the Theory of Planned Behavior (TPB). The study involved 100 undergraduate students of Bogor Agricultural University (IPB) which were selected randomly. The design of the study was cross sectional study with simple random sampling method. The results showed that attitude and intention to use was the high category, while the greatest proportion of subjective norm and behavioral control were at the middle category. Meanwhile, according to the model of Theory of Planned Behavior (TPB), attitude, subjective norm, and behavioral control had positive correlations with intention to use e-money. Attitude and subjective norm affected intention to use e-money.